A profession in crisis? Teachers' responses to England's high-stakes accountability reforms in secondary education. (September 2022) - Towers, Emma; Gewirtz, Sharon; Maguire, Meg; Neumann, Eszter
Abstract: There has been a tendency to construct the teaching profession through a narrative of 'crisis' which places particular emphasis on high rates of attrition and poor wellbeing driven by a demanding work culture. Drawing on qualitative data from a mixed-methods study, this paper examines teachers' responses to reforms to English secondary education. It presents evidence that supports a 'profession in crisis' narrative with many of the research participants expressing negative attitudes towards the reforms and concerns about staying in teaching. However, the paper also illuminates a counter-narrative that highlights teachers' job satisfaction and their desire to remain in the profession. Highlights: Dominant discourses of a 'profession in crisis' in England. Majority of participants provide evidence of crisis. A counter-narrative comprise teachers who have positive views of the profession. Danger that education research reproduces and reinforces the 'crisis' narrative.